Eastern Caribbean Currency Union : 2016 Discussion on Common Policies of Member Countries-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This IMF Staff Report for the 2016 Discussion on Common Policies of Eastern Caribbean Currency Union (ECCU) Member Countries highlights that the regional recovery in ECCU is gaining ground, supported by continued low oil prices, strong tourism arrivals, and robust citizenship-by-investment receipts. Risks to the near-term outlook are balanced, but growth in the ECCU continues to be hindered by weak competitiveness, banking sector fragilities, susceptibility to natural disasters, and large public debt. The Executive Directors have encouraged the authorities to press ahead with sound macroeconomic policies and structural reforms to decisively address these issues and strengthen the conditions for robust long term growth.